SOAL A.
(3x - 5y)•(-4x + 7y)
= (3x)•(-4x) + (3x)•(7y) + (-5x)•(-4y) + (-5y)•(7y)
= -12x² + 21xy + 20xy - 35y²
= -12x² + 41xy - 35y²
= - (12x² - 41xy + 35y²)
SOAL B.
(-2x + 3y)•(3x² - 4xy - 5y²)
= (-2x)•(3x²) + (-2x)•(-4xy) + (-2x)•(-5y²) + (3y)•(3x²) + (3y)•(-4xy) + (3y)•(-5y²)
= -6x³ + 8x²y + 10xy² + 9x²y - 12xy² - 15y³
= -6x³ + 8x²y + 9x²y + 10xy² - 12xy² - 15y³
= -6x³ + 17x²y - 2xy² - 15y³
= - (6x³ - 17x²y + 2xy² + 15y³)
SOAL C.
(x - 2y)•(3x + y)•(x² - xy - 2y²)
= (3x² + xy - 6xy - 2y²)•(x² - xy - 2y²)
= (3x² - 5xy - 2y²)•(x² - xy - 2y²)
= 3x⁴ - 3x³y - 6x²y² - 5x³y + 5x²y² + 10xy³ - 2x²y² + 2xy³ + 4y⁴
= 3x⁴ - 3x³y - 5x³y - 6x²y² + 5x²y² - 2x²y² + 10xy³ + 2xy³ + 4y⁴
= 3x⁴ - 8x³y - 3x²y² + 12xy³ + 4y⁴
SOAL D.
(-3x²y)•(x - 2y)•(3x - y)
= (-3x³y + 6x²y²)•(3x - y)
= (-3x³y)•(3x) + (-3x³y)•(-y) + (6x²y²)•(3x) + (6x²y²)•(-y)
= -9x⁴y + 3x³y² + 18x³y² - 6x²y³
= -9x⁴y + 21x³y² - 6x²y³
= - (9x⁴y - 21x³y² + 6x²y³)
[answer.2.content]